2003
DOI: 10.1103/physrevb.68.174405
|View full text |Cite
|
Sign up to set email alerts
|

Induced V and reduced Co magnetic moments at the V/Co interface

Abstract: Using x-ray magnetic circular dichroism ͑XMCD͒ the vanadium and cobalt magnetic moments at the V/Co interface have been extracted for different V and Co thicknesses. We find a large magnetic moment induced on the V that is coupled antiferromagnetic to the Co. For Co both the spin and orbital moments are reduced at the interface. The evolution of the magnetic moment together with the spectral changes in the V L 2,3 XMCD upon V deposition demonstrate the complexity of the V/Co interface as manifested in its phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
35
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 60 publications
10
35
1
Order By: Relevance
“…1, [37][38][39][40][41][42][43] The opposite sign for the XMCD signals of the hysteresis loops for V and Co in Fig. 1 provide direct evidence for the opposite magnetization of the V and Co thin layers, also in agreement with published results.…”
Section: Element-specific Xmcd Hysteresis Loopssupporting
confidence: 79%
See 3 more Smart Citations
“…1, [37][38][39][40][41][42][43] The opposite sign for the XMCD signals of the hysteresis loops for V and Co in Fig. 1 provide direct evidence for the opposite magnetization of the V and Co thin layers, also in agreement with published results.…”
Section: Element-specific Xmcd Hysteresis Loopssupporting
confidence: 79%
“…Recently, we reported the magnetic properties of V / Co and Co/ V interfaces grown on Cu͑100͒ surfaces and for very low V and Co coverages. 37 In particular, we showed that Co atoms induce a strong magnetic moment on the V atoms with opposite magnetization direction. The trends in the magnetic moments vs Co and V thicknesses showed that the Co magnetic moments decrease with decreasing Co and increasing V coverages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade great attention has been paid to the study of V / Co multilayers [1][2][3][4] due to the oscillatory exchange through V layers. These studies clearly indicated that a better understanding of the interface magnetism at the V / Co interface is mandatory to understand the physics of this system.…”
Section: Introductionmentioning
confidence: 99%